Impact of SGLT2 inhibitors on heart failure risk and kidney function in type 2 diabetic mellitus patients: A literature review - Chelsy Vanya Br. Meliala; Syahrul Tuba; Adi Priyono; Syed Azhar Syed Sulaiman; Budi Sumaryono; Endah Permata Sari (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2026)
Background: Type 2 diabetes mellitus is known to be closely associated with an increased risk of heart failure and chronic kidney disease, both of which are major causes of illness and death in diabetic patients. In recent years, sodium-glucose cotransporter-2 inhibitors (SGLT2i), which were initially developed as blood glucose-lowering drugs, have been shown to provide additional benefits beyond glycemic control, particularly in protecting the heart and kidneys. Aims: This literature review aims to comprehensively evaluate the impact of SGLT2 inhibitor use on the risk of heart failure and renal function outcomes in patients with type 2 diabetes mellitus (T2DM). Method: A literature search was conducted through the PubMed, Scopus, and ScienceDirect databases for publications from 2015 to 2025, including randomized controlled trials (RCTs), meta-analyses, and systematic reviews using the keywords "SGLT2 inhibitors," "heart failure," "renal outcomes," and "type 2 diabetes." Results: from various large clinical trials and meta-analyses show that SGLT2 inhibitors consistently reduce the risk of hospitalization due to heart failure and cardiovascular death, with a hazard ratio generally below 0.80. In addition, this therapy also slows the decline in glomerular filtration rate (eGFR), thereby reducing deaths due to renal causes. Conclusion: SGLT-2i has been shown to provide strong cardio-renal protection in patients with T2DM, especially in individuals at high risk of heart failure or chronic kidney disease, in accordance with current clinical guidelines.